Truly Tasteless Jokes xiii - Knott, Blanche, author 535485 (New York :, 1993)
From Blanche Knott, here are the usual disgusting, ribald, and otherwise offensive riddles and jokes, given out like multivitamins on a one-a-day basis for the edification and enlightenment of all mankind. Ties in with Knott's new hardcover, Blanche Knott's Treasury of Tastelessness.